Preparation and characterization of temperature-memory nanoparticles of MIP-CS-g-PMMA. Issue 112 (22nd November 2016) - Zheng, Xue-Fang; Lian, Qi; Yang, Hua; Wu, Hai-Xia; Cheng, Caihong; Yin, Gengwen; Zhang, Weiguo
Abstract : A molecular imprinted graft copolymer of chitosan with methyl methacrylate (MIP-CS- g -PMMA) was prepared by free radical polymerization with aspirin as the template molecule and ammonium persulfate as the initiator. Abstract : A molecular imprinted graft copolymer of chitosan with methyl methacrylate (MIP-CS- g -PMMA) was prepared by free radical polymerization with aspirin as the template molecule and ammonium persulfate as the initiator. The molecular imprinted polymers (MIPs) were characterized by FTIR, X-ray diffraction, thermo-gravimetric analysis, 1 H NMR, TEM and SEM. The mechanism of graft copolymerization and factors affecting the graft reaction were studied in detail, and the optimum reaction conditions (to the highest % G and % E as the standard) were obtained at a methylmethacrylate concentration of 1.2 mol L −1, chitosan concentration of 16.67 mol L −1, initiator concentration of 0.0062 mol L −1, temperature of 60 °C and reaction time of 7 h. MIP-CS- g -PMMA had not only the properties of high efficiency selective recognition adsorption to the template molecules, but also of temperature memory, which was a new type of functional polymer material.